Combining simplified DNA extraction technology and recombinase polymerase amplification assay for rapid and equipment-free detection of citrus pathogen Phytophthora parasitica - Wei-yu CHEN; Jia YU; Heng XU; Xin-yu LU; Ting-ting DAI; Yue-e TIAN; Dan-yu SHEN; Dao-long DOU (Journal of Integrative Agriculture)
Foot and root rot caused by Phytophthora parasitica is a substantial threat to citrus cultivation, affecting both yield and quality. Thus, rapid and accurate detection of P. parasitica plays an important role in disease management. The aim of this study was to develop a simple diagnostic method to detect P. parasitica infection by combining recombinase polymerase amplification and lateral flow strips (LF-RPA). To establish the LF-RPA assay of P. parasitica, the primers and probe designed based on the Ypt1 gene were tested for specificity to P. parasitica, which showed no cross-reactivity with DNAs of other related oomycete species. The LF-RPA assay detected the amount of genomic DNA of P. parasitica which was as low as 1 pg. To make the LF-RPA assay useful in low-resource settings, four simplified DNA extraction methods were compared, after which the LF-RPA assay was applied, with no specialized equipment, to analyze a diverse range of citrus tissues by using a simplified PEG-NaOH method for DNA extraction. This method was successful in detecting P. parasitica in infected plant samples within 30 min. Combining the LF-RPA assay and a simplified DNA extraction method could be a potential detection test for P. parasitica, especially in areas with limited resources.